Determinants of Agrobank selection decision: A study in northern region states of Malaysia - Siti Hajar, Mustaffa (2019)
Islamic banking has become the fastest growing industries that have been found in the last three decades through which the number of customer using Agrobank is constantly growing. The extensive numbers of customers choosing Agrobank does not only contribute to socio-economic development, but, the Agrobank development as well. Thus, the aim of the study is to examine the factors that influence bank selection decision among customers of Agrobank. This study focuses on all customers of Agrobank in Northern Region States branches in Malaysia. There are 19 branches of Agrobank in Northern Region States area where a total of 210 questionnaires have been distributed. The finding of the study indicates that 55.5 percent of the variance of factor influencing bank selection decision of Agrobank can be explained by the variables, namely bank convenience and bank reputation. Furthermore, the same factor of bank convenience and bank reputation are found significant to the selection decision of Agrobank